2019
DOI: 10.25225/fozo.069.2019
|View full text |Cite
|
Sign up to set email alerts
|

New distribution records for the endangered black-and-white snub-nosed monkeys (Rhinopithecus bieti) in Yunnan, China

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This needs to be a key part of the initial planning process, as well as an ongoing part of the land use execution. Beginning or increasing community participation, friendly development, and public involvement to work toward a sustainable and healthy increase in snub-nosed monkey habitat quality and an overall improvement in habitat ecosystem health [ 14 ]. Promoting community and public participation in the conservation of snub-nosed monkey habitat quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This needs to be a key part of the initial planning process, as well as an ongoing part of the land use execution. Beginning or increasing community participation, friendly development, and public involvement to work toward a sustainable and healthy increase in snub-nosed monkey habitat quality and an overall improvement in habitat ecosystem health [ 14 ]. Promoting community and public participation in the conservation of snub-nosed monkey habitat quality.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning or increasing community participation, friendly development, and public involvement to work toward a sustainable and healthy increase in snub-nosed monkey habitat quality and an overall improvement in habitat ecosystem health [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key drivers of its habitat loss is human disturbance, including logging, agriculture, and grazing [65]. While collaboration between the government and civil society over the past 40 years has increased the total number through the establishment of nature reserves, its vulnerability remains high due to habitat fragmentation and a small group size [66]. In order to enhance overall habitat connectivity and boost community sustainable livelihoods, the Yunnan Forestry and Grassland Administration initiated the protection network for Yunnan snub-nosed monkeys in 2019 with 13 organizations, including governmental departments, academic institutions, and non-governmental organizations based on the pilot protection project launched in 2014.…”
Section: Yunnan Snub-nosed Monkey Protection Networkmentioning
confidence: 99%
“…R. bieti occurs at altitudes from 2700 to 4600 m (Cui, 2003; Kirkpatrick, 1996). They are endemic to the Trans‐Himalaya region, which is bounded by the Yangtze River to the east and the Mekong River to the west (29.37° N and 25.52° N) (Long et al, 1994; Wang, Xu, et al, 2019). Zhou et al (2016) identified multiple hypoxia‐related genes under strong positive selection in R. bieti .…”
Section: Introductionmentioning
confidence: 99%